Pengaruh Kualitas Produk, Citra Merek dan Persepsi Harga Terhadap Minat Beli Produk Smartphone Samsung di Kota Denpasar - Prawira, Bayu; Yasa, Ni Nyoman Kerti (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the effect of product quality, brand image and perception of the price of the products Samsung smartphone buying interest in Denpasar. This study used a qualitative research using surveys and questionnaires to 112 respondents. The data analysis technique used is multiple linear regression. It was found that the quality of the product positive and significant effect on interest in buying products Samsung smartphone in Denpasar. Furthermore, brand image and a significant positive effect on buying interest products Samsung smartphone in Denpasar and price perception positive and significant effect on interest in buying products Samsung smartphone in Denpasar.
Keywords: Kualitas Produk; Citra Merek; Persepsi Harga; Minat Beli